AUTOMATED MONITORING OF THE MAIN PARAMETERS OF THE SWITCH ACTUATORS - Malovichko, V. V.; Gavryliuk, V. I. (Science and Transport Progress, 2007)
The analysis of the basic defects of the railway direct current switches with consecutive excitation have been provided, the automated device for detection of electric motors defects by a consumed current curves analyses under operating conditions at railway stations without interruption in work of switches has been proposed.